P94 Rapamycin helps maintain the regulatory phenotype of cytochrome P450IID6-specific Treg expanded from patients with autoimmune hepatitis type 2 by reducing the number of IFNγ+ cells. (6th September 2011) - Holder, B; Grant, C R; Ma, Y; Mieli-Vergani, G; Vergani, D; Longhi, M S
Abstract : Introduction: Control of T cell reactivity to cytochrome P450IID6 (CYP2D6) is key to immune-tolerance restoration in autoimmune hepatitis type 2 (AIH-2). CD4 + CD25 + regulatory T cells (Treg), central to autoreactive T cell regulation, are impaired in AIH-2. Cell therapy based on CYP2D6-specific Treg (CYP-Treg) could provide specific control over effectors of liver damage in AIH-2. We have generated CYP-Treg from AIH-2 patients and demonstrated that these cells exert greater suppression than polyclonal Treg. Whether CYP-Treg can undergo expansion maintaining their functional phenotype is untested. Aim: To assess CYP-Treg functional phenotype over 2-week expansion in AIH-2 patients. Methods: 48 CYP-Treg cell lines were obtained from 12 AIH-2 patients positive for the predisposing HLA-DR7 and DR3 alleles; 36 Treg cell lines specific for a DR7 or DR3-restricted influenza-haemagglutinin (HA) peptide were generated from 9 DR7 + or DR3 + healthy subjects (HS) and used as controls. CYP- and HA-Treg were obtained after co-culture with peptide-pulsed semi-mature DCs. T-reg were expanded for 2 weeks in the presence of: (1) IL2 (300 U/ml); (2) IL2+rapamycin (RP) to enhance Treg function; (3) IL2+IL6/IL1b, cytokines mimicking the proinflammatory milieu of AIH-2. Treg phenotype was determined by flow cytometry; frequency of cytokine-producing cells by intracellular staining. Results: Before expansion, the frequency of CD127 - and FOXP3 + cells exceeded 80% in both CYP- and HA-Treg. Compared to HA-Treg, CYP-Treg contained higher numbers of IFNg (6.4±1 vs 3.6±1.2, p=0.09), IL2 (9.5±2.6 vs 2.6±0.5, p=0.02), IL17 (7.1±1 vs 3±1.2, p=0.026), IL10 (9.1±2 vs 3.3±2.6, p=0.03) and TGFb (10.4±2 vs 3.6±0.7, p=0.001) producing cells. After expansion with IL2, CYP- and HA-Treg maintained a similarly high frequency of FOXP3 + and CD127 − cells, while frequency of IFNg + cells increased markedly (CYP-Treg: from 6.5±1 to 27±3, p<0.0001; HA-Treg: from 3.8±1.5 to 11±1.3, p<0.01). Exposure to RP decreased the frequency of IFNg + cells by 36% (p=0.04) in HS and by 30% (p=0.15) in AIH-2. Exposure of Treg to IL6/IL1b had no effect on their phenotype and cytokine production. Conclusion: Compared to HA-Treg, CYP-Treg contain higher numbers of cytokine-producing cells, possibly reflecting a higher activation state of their precursors. After expansion, antigen-specific Treg retain a classical T-reg phenotype (CD127− and FOXP3+) even upon exposure to pro-inflammatory stimuli, but contain a high proportion of IFNg + cells. Reduction of IFNg + cells in the presence of RP suggests a role for this drug in the expansion of antigen-specific T-reg for immunotherapy in AIH-2.